2012
DOI: 10.1088/0953-4075/45/20/205701
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution x-ray imaging ofKαvolume radiation induced by high-intensity laser pulse interaction with a copper target

Abstract: In a proof of principle experiment using the LULI 100-TW laser facility ELFIE, we have demonstrated high spectral and spatial resolution of K α volume radiation induced by energetic electrons generated by irradiating solid Cu targets with visible (0.53 μm) 350 fs laser pulses. Employing an x-ray spectrometer equipped with the spherically bent crystal of quartz (502) and with an image plate, single shot Cu-K α radiation was recorded in first-order reflection allowing for a geometrical mapping of the emission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The obtained results will contribute to the validation of alternate atomic structure calculations including configuration interaction effects [164,167]. The feasibility of this research was confirmed by recent experiments at laser intensities of 5 Â 10 18 À 2 Â 10 20 W=cm 2 [168,169] (see Fig. 36), where the spectrally and spatially resolved X-ray images of the Cu K a emission demonstrated the variation of the hot electron generation and propagation in a solid Cu target as a function of the laser beam focusing.…”
Section: High-field Diagnostics With X-ray Spectroscopysupporting
confidence: 58%
See 1 more Smart Citation
“…The obtained results will contribute to the validation of alternate atomic structure calculations including configuration interaction effects [164,167]. The feasibility of this research was confirmed by recent experiments at laser intensities of 5 Â 10 18 À 2 Â 10 20 W=cm 2 [168,169] (see Fig. 36), where the spectrally and spatially resolved X-ray images of the Cu K a emission demonstrated the variation of the hot electron generation and propagation in a solid Cu target as a function of the laser beam focusing.…”
Section: High-field Diagnostics With X-ray Spectroscopysupporting
confidence: 58%
“…Hot electron induced Cu K a emission observed at wedge-shaped massive copper targets. The focusing of the laser beam at variable distances above (negative value) and below (positive values) the target surface (yellow line) affects strongly the interaction conditions and the electron transport[168].…”
mentioning
confidence: 99%
“…A relatively faster scaling of 1.5 for 45 fs laser pulses was observed in our experiment. It is expected that the increased hot electron fraction with increasing laser intensity will shift the ionization balance towards higher ionization states due to the hot electron beam enhanced ionization rate in ultra-short laser-produced plasma [30], leading to the higher scaling with fs laser pulses. When the higher energy hot electrons generated with increasing laser intensity penetrate deep inside the target, K-α photons generated from the deep region of the target will be reabsorbed as they propagate out of the target surface.…”
Section: Resultsmentioning
confidence: 99%
“…Copper (Cu) is one of the most exploited elements in the various fields of industry and technology. There has been increasing interest in copper spectral characteristics in the last decade [1][2][3][4]. The spectral line characteristics of the copper atom (Cu I) and its singly charged ion (Cu II) are valuable diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%